François Grémy and the Birth of IMIA - Degoulet, P.; Haux, R.; Kulikowski, C.; Lun, K. C. (Methods of Information in Medicine, 2005)
In 2001 the International Medical Informatics Association (IMIA) approved the establishment of a Medical Informatics Award of Excellence to be given every three years to an individual, whose personal commitment and dedication to medical informatics has made a lasting contribution to medicine and healthcare through her or his achievements in research, education, development or applications in the field of medical informatics. The first award was given in 2004 to Prof. François Grémy, Uzes, France.As the first chairman and moderator of TC4, François Grémy is considered to be the first President of its renamed and refocused successor, the International Medical Informatics Association. The role of IFIP-TC4 in bringing together early health informaticians cannot be underestimated. Although TC4 was composed in large part of computer professionals interested in medical applications, Grémy recruited the first generation of IMIA officers and members from the medical and healthcare communities. Intellectually as well as organizationally, IFIP-TC4 was the true predecessor of IMIA.
Keywords: Medical informatics; IMIA